Evaluate fin performance of a space radiator to remove heat generated for outer space application - Nor Nashriq Azizi, Abd Shukor (2010)
Heat is generated in spacecrafts due to air-condition system, electronic and electrical equipment, human beings, etc. The heat generated from these sources must be removed in order to maintain the spacecraft at the required temperatures. Heat rejection to outer space is the area of present work where radiation is the dominant single mode. Extended surfaces are advantageous for this situation for heat dissipation to outer space. To simulate conditions of outer space where convection is not present is difficult and costly. Hence convection cannot be excluded in the testing of space radiator. The present analysis includes convection and irradiation terms. The physical situation considered is a horizontal fin with a rectangular cross-section. One end of the fin is maintained at a constant elevated temperature, and the fin is short and the heat loss from the tip is negligible. Heat is transferred by conduction along the fin and dissipated from the surface via natural convection and radiation. The numerical solution is obtained for the present problem by developing an algorithm where the domain is discretized by Taylor series central difference scheme and have been solved by Jacobi method, which possesses the quality of exceptional accuracy with a few numbers of nodes. The algorithm is computed using FORTRAN Software with certain parameter value. This method of approach helps to estimate its performance under actual working conditions. A comparison is made to published results, and the agreement between the present and previous is very good. Results show that the total heat loss to ambient strongly effected by convection and radiation. In the absence of convection, the efficiency is decrease with the increasing of radiation parameter. It is also show that increasing of radiation parameter will increase the total heat transfer to ambient. Longitudinal heat conduction parameter will increase the amount of heat dissipated to ambient. Because of several limiting assumptions, the results would be used only for preliminary analysis and design particularly when a fin assembly is involved rather than an individual fin.